2020
DOI: 10.1175/jcli-d-19-0647.1
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Zonally Asymmetric Stratospheric Ozone Changes on the Arctic Polar Vortex Shift

Abstract: Recent studies have found a shift of the Arctic stratospheric polar vortex toward Siberia during late winter since 1980, intensifying the zonally asymmetric ozone (ZAO) depletion in the northern middle and high latitudes with a stronger total column ozone decline over Siberia compared with that above other regions at the same latitudes. Using observations and a climate model, this study shows that zonally asymmetric stratospheric ozone depletion gives a significant feedback on the position of the polar vortex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 64 publications
(72 reference statements)
0
7
0
Order By: Relevance
“…Many operational forecast and reanalysis systems as well as climate models neglect possible impacts of stratospheric ozone on surface climate by prescribing a diagnostic ozone forcing [22,23,24], thus ignoring ozone feedbacks. Furthermore, they typically use a zonally averaged ozone climatology, whereas a longitudinally resolved ozone forcing may better represent the climatology and trends of the Arctic polar vortex and surface climate, as idealized model experiments show [25,26,27]. However, the importance of the spatial structure during Arctic ozone depletion is still unclear.…”
mentioning
confidence: 99%
“…Many operational forecast and reanalysis systems as well as climate models neglect possible impacts of stratospheric ozone on surface climate by prescribing a diagnostic ozone forcing [22,23,24], thus ignoring ozone feedbacks. Furthermore, they typically use a zonally averaged ozone climatology, whereas a longitudinally resolved ozone forcing may better represent the climatology and trends of the Arctic polar vortex and surface climate, as idealized model experiments show [25,26,27]. However, the importance of the spatial structure during Arctic ozone depletion is still unclear.…”
mentioning
confidence: 99%
“…Stratospheric chemical composition changes Atmospheric chemistry plays a critical role in modulating global climate. Climatic impacts of stratospheric ozone, which is both radiatively and chemically active, have been well documented in the literature (e.g., de F. Forster and Shine, 1997; Son et al, 2009Son et al, , 2010Hu et al, 2015;Nowack et al, 2015Nowack et al, , 2018Xie et al, 2016;Maleska et al, 2020;Zhang et al, 2020a;Friedel et al, 2022;Oh et al, 2022). Apart from ozone, ODSs, aerosols, water vapor, and GHGs in the stratosphere all have an impact on global climate through radiative or chemical processes and chemical-radiative-dynamic feedbacks.…”
Section: The Stratospheric Chemistry and Climate Interactionmentioning
confidence: 95%
“…As for the changes in SPV position, Zhang et al (2016) found that the Arctic SPV in February shifted towards Eurasia during 1980-2016. Moreover, notably, the extent of the polar vortex shift in the last decade (2010s) compared to the 1980s was smaller than before (Zhang et al, 2020a), suggesting that there is a decadal variability in the SPV position, which is related to the internal variability in the climate system (Seviour, 2017;Zhao et al, 2022). In addition, various climate variabilities could influence the SPV position (Huang et al, 2018;Zhang et al, 2019a).…”
Section: Role Of Stratospheric Thermodynamics In Climatic Variability...mentioning
confidence: 99%
See 2 more Smart Citations